Successful CAD/CAM mouth rehabilitation following conservative TMD therapy - Tatjana Dostálova (Wolters Kluwer Medknow Publications, 2016)
Background and Aim: Temporomandibular disorders (TMDs) are clinical issues involving the masticatory muscles and the temporomandibular joints (TMJ) and associated structures, or both. The role of denture status in TMD is disputed. The aim of this study was to examine the remodeling of occlusion and TMJ paths with a resulting reduction in pain. Materials and Methods: The study group consisted of 115 patients with TMJ pain. A gradual analysis of TMJ was carried out. Twenty four different measurements were used as determinates of the skeletal sagittal jaw relationship. Based on the computer data analysis the prosthetic reconstruction was prepared. Results: Anatomical landmarks have a direct influence on function changes in TMJ areas. Significant differences were observed in posterior face height (PFH) and anterior face height (AFH). Changes in joint path angle/horizontal condylar inclination increased. The unpleasant feeling was reduced following treatment. Conclusions: Loss of occlusal stability may result in the repeated fracture of restorations and teeth and increased mobility and drifting.